PELAKSANAAN GOOD GOVERNANCE DALAM PENYUSUNAN RKP DESA DI DESA SUNGAI PASIR PUTIH KECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU TAHUN 2018 DAN 2019 - Padila Rusadi; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The implementation of Good Governance in the preparation of the Village RKP in Sungai Pasir Putih Village, Kelayang District, Indragiri Hulu Regency in 2018 and 2019 was categorized as unfavorable. This can be seen from the results of the research that the author has conducted that in the preparation of the RKP Desa there are still many principles of good governance that have not been implemented. The formulation of the problem in this research is how the implementation of Good Governance in the preparation of the Village RKP in Sungai Pasir Putih Village, Kelayang District, Indragiri Hulu Regency in 2018 and 2019. This study aims to describe the implementation of Good Governance in the preparation of the Village RKP in Sungai Pasir Putih Village, Kelayang District, Indragiri Regency. Hulu in 2018 and 2019. This research uses qualitative research methods with descriptive research types that describe problems and solutions for research subjects clearly and in detail. The results of the study state that the implementation of the principles of good governance in the preparation of the Village RKP has not all been implemented, the principles that have been implemented are inclusiveness, performance, and direction. Meanwhile, the principles of good governance that have not been implemented are justice, transparency, legitimacy, accountability, and capability..    Keywords : Good Governance ; Government Work Plan